Spatial and temporal variations of physical-chemical water quality and some heavy metals in water, sediments and fish of the Mae Kuang River, northern Thailand - Chitmanat C. (2014)
The present study was conducted to investigate heavy metal (Cd, Pb & Zn) contaminants in water, sediments and fish of the Mae Kuang River, Northern Thailand during July, 2008-June, 2009. It was found that the worst water qualities in dry seasons were caused by low water flow, municipal effluents and industrial discharges. The surface water in the river was classified into class 3-4 referring to medium-fairly clean water used for consumption after special water treatment. Pb and Cd in water were below detection limits, while Zn concentrations in water ranged 0.01-0.11 mg L-1. The Pb, Cd and Zn concentrations in sediment were 3.13-27.56, <0.02-0.43 and 3.42-10.32 mg kg-1, respectively. No Cd and Pb residues were found in Henicorhynchus siamensis and Puntioplites proctozysron flesh, while the concentrations of Zn in these fish were 4.57-6.58 mg kg-1. On the other hand, Pb and Cd residues in snakehead fish (Channa striata) were <0.05-2.13 and <0.02-0.24 mg kg-1 wet weight, while the concentrations of Zn in these fish were 3.37-12.19 mg kg-1. This information provides a useful reference in heavy metal contamination in the Mae Kuang River for river management. © 2010 Friends Science Publishers.